The adnexal mass: Benign or malignant? Evaluation of risk of malignancy index - Nahar, Shamsun; Shamsuddin, Latifa (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Screening programme for ovarian malignancy is an international public demand. Ojective: To validate a risk of malignancy index (RMI) incorporating serum CA125, abdominal ultrasound findings and menopausal status for preoperative diagnosis of ovarian malignancy among patient with adnexal mass. Methods: This prospective observational study was conducted on 57 patients having adnexal mass admitted consecutively for surgical exploration in BSMMU from January 2000 to March 2001. S. CA125 assay & abdominal ultrasonography was done within 10 days preoperatively. Ultrasound score (0, 1 & 3) using 5 sonographic features & menopausal score (1 & 3) were calculated. RMI was detected by the formula "RMI = Ultrasound score - Menopausal score - S. CA125 level" Definitive diagnosis was based on histopathological examination. See PDF for the rest of the abstract.